Teacher's Strategy for Developing Children's Creativity through the Use of Natural Materials for Collage Making - Sitti Muliya Rizka; Thalitha Zada; Siti Mirilda Putri (Universitas Pendidikan Indonesia, 2024)
This study aims to find out the teacher’s strategy in developing children’s creativity through the use of natural materials in making collages in class B1 TK Cendekia Tungkop Aceh Besar. This study used a qualitative approach with phenomenological research. The subjects of the study were 2 class B teachers and 1 principal. The data was collected through observation, interviews, and documentation, and was analyzed by using data reduction, data presentation, and concluding. The results revealed that the teachers used the central learning model with demonstration and response to questions methods in developing children’s creativity through the use of natural materials in making collages from coconut dregs. The teachers planned two activities and switched on once the first one was completed. The teachers presented colour symbols on the worksheet to help students remember and classify the colours when creating collages. The teachers explained, provided examples of how to stick, gave direction, supported, approached, and directed the students until they were able to complete the project. The teacher went around controlling the children’s progress by asking questions to ensure that the children understood the colours and how to make collages. Once the activity was finished, the teacher asked the children the same questions again. When the children remained silent and did not respond to the question, the teacher asked the questions one by one so that the children could respond to the teacher's questions.